The Burden of Respiratory Syncytial Virus in Children Under 2 Years of Age in a Rural Community in Maharashtra, India. (2nd September 2021) - Satav, Ashish; Crow, Rowena; Potdar, Varsha; Dani, Vibhawari; Satav, Shilpa; Chadha, Mandeep; Hessong, Danielle; Carosone-Link, Phyllis; Palaskar, Sameer; Simões, Eric A F
Abstract: Background: Globally, respiratory syncytial virus (RSV) is a common cause of acute lower tract infection (LRTI) in children younger than 2 years of age, but there are scant population-based studies on the burden of RSV illness in rural communities and no community studies in preterm infants. Methods: Active surveillance of LRTI was performed in the community and hospital setting for the population of 93 tribal villages in Melghat, Central India, over 4 respiratory seasons. A nasopharyngeal swab was obtained from cases presenting as a severe LRTI for molecular analysis of respiratory pathogens including RSVA and B. Results: High rates of RSV-associated LRTI were found in preterm and term infants beyond 6 months of age, extending into the second year of life. Community severe RSV LRTI rates for 0–11 months of age was 22.4 (18.6–27.0)/1000 child-years (CY) and the hospital-associated rate was 14.1 (11.1–17.8)/1000 CY. For preterm infants, these rates were 26.2 (17.8–38.5)/1000 CY and 12.6 (7.2–22.0)/1000 CY. Comparable rates in the first 6 months were 15.9 (11.8–21.4)/1000 CY and 12.9 (9.3–18.0)/1000 CY in term infants and 26.3 (15.4–45.0)/1000 CY and 10.1 (4.2–24.2)/1000 CY for preterms. The single RSV B season had higher incidences of RSV LRTI in every age group than the 2 RSV A seasons in both preterm and term infants. There were 11 deaths, all term infants. Conclusions: Studies restricted to the healthcare settings significantly underestimate the burden of RSV LRTI and preterm and term infants have comparable burdens of disease in this rural community.